2018
DOI: 10.2989/16085906.2018.1488266
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to antiretroviral therapy initiation for HIV-positive children aged 2–18 months in Swaziland

Abstract: Although early antiretroviral therapy (ART) reduces HIV-related mortality in children by up to 75%, almost half of HIV-positive children younger than 1 year old in Swaziland do not initiate ART. This study was conducted to identify barriers to early ART initiation among HIV-positive infants. This was a case-control study among HIV-positive infants, aged 2 to 18 months, who either did not initiate ART (cases), or initiated ART (controls), during 18 months after testing. Multivariable logistic regression showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The frequency of visiting a clinic, distance to the nearest clinic, and caregiver relationship with their health provider were observed in Swaziland. 8 Another study in Kahama district in north-western Tanzania found a lack of transport fare and long distance to the health facility being barriers to attending clinics for ART uptake in children. 9 The same study also observed that being divorced or widowed and primary education level of the caregivers were associated with poor uptake of ART in children.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of visiting a clinic, distance to the nearest clinic, and caregiver relationship with their health provider were observed in Swaziland. 8 Another study in Kahama district in north-western Tanzania found a lack of transport fare and long distance to the health facility being barriers to attending clinics for ART uptake in children. 9 The same study also observed that being divorced or widowed and primary education level of the caregivers were associated with poor uptake of ART in children.…”
Section: Introductionmentioning
confidence: 99%
“…For PLWHA, their needs go beyond treating the disease and involve an entire emotional and social context that permeates the difficulties in dealing daily with situations such as depressive symptoms, stigma, discrimination, a reframing of their life history, in addition to adverse effects related to the therapeutic regimen. From the analysis, it was possible to identify five critical attributes (4) : patient's refusal to follow the therapeutic plan (7,(9)(10)13,21,(23)(24)(25)27,(31)(32)34,37,(40)(41)(45)(46)49,51) ; abandonment of treatment leading to ineffective results and worsening of symptoms (8,11,14,(16)(17)22,26,(28)(29)(35)(36)(38)(39)42,44,46,(48)(49)(50) ; difficulty in reaching goals agreed between the person and the health professional (6,12,15,(18)(19)(20)37,…”
Section: Critical Attributesmentioning
confidence: 99%
“…The antecedents of the concept are shown in Chart 2 and its consequences in Chart 3, in association with related factors and defining characteristics, respectively, both expressed in the NANDA-I taxonomy with reference to the diagnosis "Ineffective Health Control". Alcohol use (9,21,25,31,(33)(34)40) NM Side effects to medications (7,11,14,(17)(18)22,45) NM Depression (9,14,16,24,(32)(33)49) NM Use of illicit drugs (17,21,23,25,31,33) NM Stigma (8)(9)11,20,50) NM Low education level (8,(14)(15)31,33) NM Anxiety (16)(17)24,(32)(33) NM Financial difficulties (8,20,26,31,43) Perceived barrier Difficulty of adequate access to care (7)…”
Section: Background and Consequencesmentioning
confidence: 99%
See 2 more Smart Citations